P0794A REAL-WORLD OBSERVATIONAL STUDY OF ETELCALCETIDE USE IN HEMODIALYSIS PATIENTS WITH SECONDARY HYPERPARATHYROIDISM IN EUROPE. (6th June 2020) - Louie, Karly; Papadopoulou, Dorothea; Hoffmann, Maxime; Manrique Escola, Joaquin; Kohnle, Matthias; Cejka, Daniel; Piccoli, Giorgina; Rix, Marianne; Boots, Johannes; Marn Pernat, Andreja; Torregrosa, Vicente; Tsirtsonis, Kate; et al.
Abstract: Background and Aims: Intravenous etelcalcetide was approved in Europe in 2016 for treatment of secondary hyperparathyroidism (SHPT) in adult patients on hemodialysis (HD). Data on real-world use of etelcalcetide are needed to inform clinicians on routine clinical practice with this newly approved therapy. Method: A multi-country observational medical chart review study was performed to describe clinical management of patients treated with etelcalcetide. Sites with at least 6 months of use of etelcalcetide were eligible for study participation. Chronic HD patients who had at least one record of etelcalcetide prescription were recruited. Abstracted data included demographics, clinical history, laboratory parameters and etelcalcetide use over time. Interim data are being reported. Results: Medical charts for 238 HD patients who started etelcalcetide between December 24, 2016 and June 7, 2019 were reviewed. Data were obtained from 47 sites from 9 countries (Austria, Denmark, France, Germany, Greece, Netherlands, Russia, Slovenia, and Spain). Forty eight percent of patients (113/238) switched from cinacalcet to etelcalcetide (≤90 days from last cinacalcet prescription), whereas the remaining 125 patients were calcimimetic naive. Median (interquartile range, IQR) age was 62.5 (52-74) and dialysis vintage was 4.7 years (2.4-8.7). Twenty four percent of patients were diabetic and 17% of patients had a history of at least one cardiovascular event (heart failure, myocardial infarction, peripheral vascular disease, or stroke). Parathyroidectomy had been performed in 6% (13/238) of patients and 11% (26/238) had received a kidney transplant. Two-thirds of patients (63%) had a starting etelcalcetide dose of 5 mg and the median weekly dose was 7.5 mg (range: 2.5-15 mg). Table 1 summarizes the median and IQR for parathyroid hormone (PTH), calcium (Ca) and phosphate (P) levels at baseline, 3, 6 and 12 months following etelcalcetide initiation. At baseline, 85% (201/237) had normal Ca (≥2.1 mmol/L). Among patients who had a normal Ca at baseline, the cumulative incidence of hypocalcemia (<2.1 mmol) at 3, 6, 9 and 12 months was, 31%, 45%, 57% and 63%, respectively. Median time to first hypocalcemia event (Kaplan-Meier estimation) was 6.9 months (95% CI: 5.4, 8.9). Etelcalcetide persistence at 3, 6, 9 and 12 months was 96%, 94%, 91% and 87%, respectively. Of the 40 patients who discontinued etelcalcetide by 12 months, 10 patients discontinued for side effects (hypocalcemia=6, nausea=3, and vomiting=1), 5 for parathyroidectomy, 9 for low PTH, 1 for high PTH, and 15 for other reasons. More than half of the patients achieved a >30% reduction in PTH from baseline at 6-months (55.9%) and 73.5% at 12 months; and it was 63.2% and 80% for patients who were calcimimetic naive and 47.8% and 66.4% for patients who switched from cinacalcet to etelcalcetide, respectively. Conclusion: To date, this is the largest study on real-world etelcalcetide use in Europe. Etelcalcetide switchers had higher PTH levels than calcimimetic naive patients at initiation. Persistence of etelcalcetide remained high at 12 months. As expected, we observed a substantial reduction in PTH, Ca, and P, and this was greater among patients who were calcimimetic naive than switchers (-43% vs. -32% at 12 months) for PTH. No new safety signals were observed.